A new Brazilian stag beetle of the genus Sclerostomus Burmeister, 1847 (Insecta: Coleoptera: Lucanidae) - Grossi, P. C.; Racca-Filho, F. (Zootaxa, 2004)
A new species of the lucanid genus Sclerostomus Burmeister, 1847 (subgenus Altitatiayus Weinreich, 1960), S. trifurcatus sp. n., from the Itatiaia Mountains of the Brazilian Minas Gerais State, is described and illustrated. This new species is readily distinguished from all other species in the genus by the trifurcate apex of the mandible, and by the presence of a conspicuous tubercle on the frons.